Formulation of Hand Sanitizer Gel Jatropha Sap (Jatropha curcas L) as Antiseptic - Siswati Siswati; Fika Aryati; Angga Cipta Narsa (Journal of Tropical Pharmacy and Chemistry, 2022)
Jatropha curcas (Jatropha curcas L) is a medicinal plant that is often used, especially its sap. Jatropha sap contains secondary metabolite compounds in the form of saponins, flavonoids, and tannins which have antibacterial activity. This study aims to determine the antibacterial activity of Jatropha sap against Escherichia coli and Staphylococcus aureus, to determine the antibacterial activity of jatropha hand sanitizer gel preparation against Escherichia coli and Staphylococcus aureus, and to find out the best formula for hand sanitizer gel from jatropha that has antibacterial effectiveness against Escherichia coli and Staphylococcus aureus. This research was conducted by formulating hand sanitizer gel from jatropha sap with various concentrations. Based on the research data, the best data obtained for the concentration of jatropha sap which has antibacterial activity against Escherichia coli and Staphylococcus aureus is 10% with inhibition values of 13,33 ± 0,57 and 12,86 ± 0,51 the best concentrations of gel preparations. Hand sanitizer from jatropha sap which has antibacterial activity against Escherichia coli and Staphylococcus aureus is 10% with inhibitory value of 12,63 ± 0,35 and 12,10 ± 0,17 and the best formula for hand sanitizer gel contains jatropha sap fence with a concentration of 5% with a diameter value of 6,36 cm, pH 4,89, a viscosity of 4,60 ± 0,14 Pa.S, a clear whitish color with a gel-shaped texture and a homogeneous preparation.